STRATEGI PERSONAL SELLING WIRANIAGA FUJIFILM CABANG BANDUNG DI MASA PANDEMI COVID-19 - Riska Nursari; Rita Herlina (SENGKUNI Journal (Social Science and Humanities Studies), 2020)
Fujifilm's new strategies and innovations to attract consumers to buy in the middle of the Covid-19 pandemic is the attraction of researchers to examine the Bandung Branch's Personal Selling Strategies for Fujifilm Sales in the Covid-19 Pandemic. This study aims to determine the commitment, communication techniques and how to handle complaints made by Fujifilm salespeople in increasing customer confidence. The methodology used in this study is a qualitative method with a descriptive study approach. Data collection techniques used were interviewees. The results of this study indicate that Fujifilm's sales force succeeded in overcoming and maintaining consumer confidence. Despite the conditions in the Covid-19 pandemic, Fujifilm's sales force continued to carry out its role even though not face-to-face but continued to communicate using communication tools, finding customers, pre-approaching, making presentations and demonstrations, overcoming objections, following up and maintaining, closing. Fujifilm salespeople maintain a good relationship with consumers and can meet the needs of these consumers while at home during the Covid-19 pandemic.